MULTIPLE BONE CYSTS CAUSED BY THE INTAKE OF LEFLUNOMIDE IN A FEMALE PATIENT WITH RHEUMATOID ARTHRITIS - L. I. Alekseeva; N. G. Kashevarova; E. A. Taskina; Ya. A. Sigidin (Научно-практическая ревматология)
The paper describes a clinical case of adverse reaction (AR) to leflunomide (LEF) in a female patient with rheumatoid arthritis (RA). In 2007 to 2017, the female patient with a reliable diagnosis of RA took LEF (Arava) at a dose of 20 mg/day, which showed a good clinical effect. However, the patient developed atypical bone cysts in the hands, feet, right elbow, and left heel 10 years after start of therapy. The differential diagnosis with deep mycosis, tuberculosis, cancer pathology, endocrine system disease, and AR to the long-term use of LEF was made to clarify the nature of bone cysts.